Reasons to reduce alcohol consumption in university students - Conde, Karina (2017)
The reasons to reduce alcohol consumption may be defined as the causes leading a person to decrease alcohol consumption or to stay sober. This topic is not often widely studied, particularly in Latin American countries and at-risk populations. The aim of this sequential exploratory research was to explore, through an open question, the reasons why university students (N = 100) of the city of Mar del Plata, Argentina, changed their alcohol consumption. Additionally, the description was based on previous heavy episodic alcohol consumption, disorders caused by alcohol use, and participants’ gender. The results indicate that almost all studied groups reduced alcohol consumption due to their distaste or indifference for the substance. However, when disorders caused by alcohol use were severe or moderate, differences were observed. The theoretical contributions of this research are discussed, including the understanding of what leads each group to change its alcohol consumption, and the implications for the development of specific interventions based on this information.